Spinal‐Related Musculoskeletal Determinants of Functional Abdominal Bloating and Distension: A Narrative Review - Rezvan Ghomash Baf Zadeh; Tayebeh Roghani; Amy Gladin; Wendy B. Katzman; Fateme Bokaee; Peyman Adibi (Health Science Reports, 2025)
ABSTRACT Background and Aims Functional abdominal bloating and distension disorder (FABD) is a single‐syndrome gastrointestinal disorder of the “gut–brain axis,” and is associated with a negative impact on adult's well‐being. Abdomino‐phrenic dyssynergia has recently been recognized as an important contributing factor to FABD, yet the influence of other spinal musculoskeletal determinants of this gastrointestinal disorder is not known. Our aim was to qualitatively explore spinal musculoskeletal determinants and propose research on potential new treatments for FABD. Methods In this narrative review, observational and intervention studies describing terminology, proposed pathophysiology, and interventions with focus on modifiable musculoskeletal determinants of FABD were reviewed from inception through 2023. Databases of PubMed, Scopus, Google Scholar, and ISI Web of Science were searched using the following keywords: “functional abdominal bloating,” “abdominal bloating,” spine,” Abdomino‐phrenic dyssynergia,” “abdominal wall,” “pelvic floor,” “back extensor muscle.” Results This review included 65 studies. These studies were explored in three sections: Abdomino‐phrenic dyssynergia, pelvic floor function, and sagittal alignment of spine. Although most of included articles reported APD as the main contributing factor to FABD, other spinal‐related musculoskeletal factors, abdominal muscle weakness, pelvic floor dyssynergia, and spinal malalignments were considered. These musculoskeletal factors were reviewed as both evidence of FABD (direct evidence) and other disorder of gut–brain interactions (DGBIs) (indirect evidence). Conclusion Preliminary evidence suggests spinal musculoskeletal factors contribute to FABD; however, more high‐quality observational studies exploring relationships between FABD and spinal‐based musculoskeletal factors are needed.